2020
DOI: 10.1001/jamanetworkopen.2020.1541
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hormone-Modulating Breast Cancer Therapies and Incidence of Neurodegenerative Outcomes for Women With Breast Cancer

Abstract: IMPORTANCE The association between exposure to hormone-modulating therapy (HMT) as breast cancer treatment and neurodegenerative disease (NDD) is unclear. OBJECTIVE To determine whether HMT exposure is associated with the risk of NDD in women with breast cancer. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study used the Humana claims data set from January 1, 2007, to March 31, 2017. The Humana data set contains claims from privatepayer and Medicare insurance data sets from across the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…We did not find evidence to support an association between ET in the definitive treatment of non-metastatic breast cancer and dementia risk, which differs from some prior studies showing a protective effect. 3 , 5 We found that 10.2% of individuals in the ET group and 13.9% of individuals in the no-ET had dementia, which is in line with the 11.5% of Medicare Fee‐for‐Service beneficiaries aged ≥65 years with dementia. 10 Our analysis showed a protective effect of ET on dementia in fully adjusted models that completely attenuated when accounting for the competing risk of death, which is critical when examining incident outcomes in older individuals 7 and was not accounted for in all prior studies.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We did not find evidence to support an association between ET in the definitive treatment of non-metastatic breast cancer and dementia risk, which differs from some prior studies showing a protective effect. 3 , 5 We found that 10.2% of individuals in the ET group and 13.9% of individuals in the no-ET had dementia, which is in line with the 11.5% of Medicare Fee‐for‐Service beneficiaries aged ≥65 years with dementia. 10 Our analysis showed a protective effect of ET on dementia in fully adjusted models that completely attenuated when accounting for the competing risk of death, which is critical when examining incident outcomes in older individuals 7 and was not accounted for in all prior studies.…”
Section: Discussionsupporting
confidence: 80%
“…Our study accounted for the competing risk of death when analyzing the association of ET use and dementia risk and this may primarily explain the difference between our results and those observed in prior studies showing a protective effect. 5 A competing risk is an alternative outcome, such as death, that alters the probability of the outcome of interest. In traditional survival analyses individuals who are censored for any reason are considered at risk for the primary outcome for the remaining duration of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them were two breast cancer drugs (exemestane and estradiol). The use of aromatase inhibitors in BRCA treatment has recently been found to reduce the risk of AD as well as other dementias [110], and new evidence suggests that estradiol replacement therapy could prevent the tau protein from adopting its pathological conformation, helping to prevent AD [111]. Additionally, epidemiological data suggest that estrogen replacement therapy significantly decreases the risk of the onset and development of AD and PD.…”
Section: Discussionmentioning
confidence: 99%
“…From this analysis, the most impactful risk factors that target biological mechanisms and pathways underlying AD risk include the metabolic, immune, cardiovascular, and endocrine systems. 9 , 33 , 47 , 48 , 49 , 50 …”
Section: Discussionmentioning
confidence: 99%